O'Gorman, Kahlo, Rivera : encuentro para una arquitectura revolucionaria - Jerez González, Javier; Instituto Politécnico Nacional (Mexico) (Mexico City : IPN ; Ciudad Autónoma de Buenos Aires : Diseño, 2021)
In the summer of 1932, Juan O'Gorman, a very young architect who has not yet graduated, finished in Mexico City the construction of the studio houses that he had designed for Diego Rivera and Frida Kahlo. Behind a palisade of cacti, two almost perfect cubes - one painted an intense blue of red and the other white - rise on thin columns of bare concrete before the astonished gaze of everyone. The houses have a strange appearance and are not like any work that has been done before in Mexico. Its construction is extremely rational and efficient, but at the same time its structure, its volumes and holes are matched with an unusual plasticity and generate a markedly dreamlike atmosphere. They constitute a true architectural masterpiece, a strange fruit that emerges unexpectedly from the hand of a stranger. However, behind this work there is a whole story that goes back many years ago, a story that intimately links architecture with painting through political commitment. Countless relevant figures participate in it -Edward Weston, Tina Modotti, Manuel Álvarez Bravo, Carlos Obregón Santacilia, José Antonio Cuevas, Guillermo Zárraga, Le Corbusier, Vladimir Mayakovsky, Moisei Ginzburg, Sergei Eisenstein, Alfred Barr, Lev Trotsky, Henry Ford, Albert Kahn - in a framework that links Mexico City with cities as distant as Paris, Moscow and Detroit. That story, the long prelude to extraordinary architecture, is what this book tells.
Las extrañas casas para Diego y Frida: insólita arquitectura -- Por una arquitectura revolucionaria -- Trotsky y Novi ByT -- Ecos de vanguardia -- Encuentro para la revolución -- OœGorman, punto y aparte.
Incluye referencias bibliográficas (páginas 216-227).
En español.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2022. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: O'Gorman, Juan, -- 1905-1982.; Rivera, Diego, -- 1886-1957 -- Hogares y rincones; Kahlo, Frida, -- 1907-1954 -- Hogares y rincones; Funcionalismo (Arquitectura) -- Mexico -- Ciudad de México.; Arquitectura doméstico -- México -- Ciudad de México -- Historia -- Siglo XX; Álvaro Obregón (Ciudad de México, México) -- Edificios, estructuras, etc; Libros electrónicos.